Characteristics of a nationwide cohort of patients presenting with isolated hypogonadotropic hypogonadism (IHH). Issue 1 (January 2018) - Bonomi, Marco; Vezzoli, Valeria; Krausz, Csilla; Guizzardi, Fabiana; Vezzani, Silvia; Simoni, Manuela; Bassi, Ivan; Duminuco, Paolo; Di Iorgi, Natascia; Giavoli, Claudia; Pizzocaro, Alessandro; Russo, Gianni; et al.
Abstract : Objective: Isolated hypogonadotropic hypogonadism (IHH) is a rare disorder with pubertal delay, normal (normoosmic-IHH, nIHH) or defective sense of smell (Kallmann syndrome, KS). Other reproductive and non-reproductive anomalies might be present although information on their frequency are scanty, particularly according to the age of presentation. Design: Observational cohort study carried out between January 2008 and June 2016 within a national network of academic or general hospitals. Methods: We performed a detailed phenotyping of 503 IHH patients with: (1) manifestations of hypogonadism with low sex steroid hormone and low/normal gonadotropins; (2) absence of expansive hypothalamic/pituitary lesions or multiple pituitary hormone defects. Cohort was divided on IHH onset (PPO, pre-pubertal onset or AO, adult onset) and olfactory function: PPO-nIHH ( n = 275), KS ( n = 184), AO-nIHH ( n = 36) and AO-doIHH (AO-IHH with defective olfaction, n = 8). Results: 90% of patients were classified as PPO and 10% as AO. Typical midline and olfactory defects, bimanual synkinesis and familiarity for pubertal delay were also found among the AO-IHH. Mean age at diagnosis was significantly earlier and more frequently associated with congenital hypogonadism stigmata in patients with Kallmann's syndrome (KS). Synkinesis, renal and male genital tract anomalies were enriched in KS. Overweight/obesity are significantly associated with AO-IHH rather than PPO-IHH. Conclusions: Patients with KS are more prone to develop a severe and complex phenotype than nIHH. The presence of typical extra-gonadal defects and familiarity for PPO-IHH among the AO-IHH patients indicates a common predisposition with variable clinical expression. Overall, these findings improve the understanding of IHH and may have a positive impact on the management of patients and their families.